2023
DOI: 10.1002/fsn3.3850
|View full text |Cite
|
Sign up to set email alerts
|

Higher anthocyanin intake is associated with lower depressive symptoms in adults with and without major depressive disorder

Annika Mestrom,
Karen E. Charlton,
Susan J. Thomas
et al.

Abstract: BackgroundMajor depressive disorder (MDD) is a significant cause of disability globally and an emerging body of evidence suggests that dietary components, including flavonoids, may impact depression‐related biochemical pathways. Further research that characterizes dietary intake of flavonoids in diverse population groups, including people with MDD and explores the relationship between flavonoid intake and depression is needed. This study aimed to determine dietary flavonoid and subclass intake and assess the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The inclusion of self-reported cognitive outcomes may be particularly important, given that self-reported cognitive complaints have been associated with Alzheimer's disease risk and pathology [54,55]. On a related note, given the known impact of nutritional interventions rich in anthocyanin/anti-inflammatory properties on other aspects of mental health (depression, anxiety, and stress [11][12][13]) and sleep health [11,14] in adults without cognitive impairment, future studies in MCI should also examine the impact of American elderberry juice on a broader range of outcomes beyond cognition and inflammation. Fourth, the present study did not assess the influence of other factors that may have anti-inflammatory properties and impact blood-based inflammatory markers and cognitive functioning in MCI, such as diets (e.g., Mediterranean diet rich in omega-3 fatty acids, antioxidants, and polyphenols [56]), medications, and vitamins [57,58]).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of self-reported cognitive outcomes may be particularly important, given that self-reported cognitive complaints have been associated with Alzheimer's disease risk and pathology [54,55]. On a related note, given the known impact of nutritional interventions rich in anthocyanin/anti-inflammatory properties on other aspects of mental health (depression, anxiety, and stress [11][12][13]) and sleep health [11,14] in adults without cognitive impairment, future studies in MCI should also examine the impact of American elderberry juice on a broader range of outcomes beyond cognition and inflammation. Fourth, the present study did not assess the influence of other factors that may have anti-inflammatory properties and impact blood-based inflammatory markers and cognitive functioning in MCI, such as diets (e.g., Mediterranean diet rich in omega-3 fatty acids, antioxidants, and polyphenols [56]), medications, and vitamins [57,58]).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Cognitive decline has been linked with inflammation [4,5], which has been proposed as an underlying mechanism contributing to Alzheimer's disease and is a promising target for intervention [6]. Elderberries have anti-inflammatory and antioxidant properties [7,8], and show promising potential effects for improving cognition [9,10] and other areas of mental health [11][12][13] and related functioning [11,14]. However, to date, there have been no randomized controlled studies comparing the effects of elderberry consumption relative to a placebo-control in individuals with MCI.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study examined the consumption of anthocyanins in 93 diverse groups, including those with major depressive disorder (MDD) and healthy individuals. The study found that those with MDD had insufficient intake of anthocyanins in their diet, and increased consumption of anthocyanins was linked to reduced depressive symptoms in the overall group [ 88 ]. A recent study conducted on 50 hypertensive patients used a randomized, triple-blind, placebo-controlled crossover design.…”
Section: Role and Mechanisms Of Polyphenols In The Treatment Of Nervo...mentioning
confidence: 99%